The effect of endurance training on changes in purine metabolism: a longitudinal study of competitive long-distance runners - Zielinski, J.; Rychlewski, T.; Kusy, K.; Domaszewska, K.; Laurentowska, M. (European Journal of Applied Physiology, 2009)
The purpose of the study was to characterize the changes in purine metabolism in long-distance runners in the main phases of their 1-year training cycle. Nine male athletes competing in distances 5 and 10 km at national/regional level, mean age 22.9± 0.6 years, practising sport for 8.6 ± 0.3 years, participated in the study. The changes in plasma concentrations of hypoxanthine (Hx), xanthine (X) and uric acid (UA) and the activity of the enzyme HGPRT in red blood cells haemolysate were followed in four characteristic points of the annual training cycle: preparatory phase (specific subphase), competition period, transition period and preparatory phase (intermediate subphase). Resting and postexercise plasma concentrations of X and, Hx and HGPRT activity changed significantly during 1-year training cycle. Significant changes in postexercise Hx values between training phases were found, from 9.3 µmol/l in competition period to 22.9 µmol/l in transition period (Friedmann`s ANOVA, P < 0.01). Postexercise UA values ranged from 371 to 399 µmol/l and did not change significantly between training phases. An increase in resting (from 52.0 to 58.4 IMP mg-1 Hb min-1, P < 0.05) and postexercise (from 70.7 to 76.2 IMP mg-1 Hb/min, not significant) HGPRT activity between the specific preparation and competition period was observed. In the transition period, Hx postexercise concentration increased (22.9 µmol/l, P < 0.01) and HGPRT postexercise activity decreased (58.8 IMP mg-1 Hb/min, P < 0.01) significantly. The results indicate that the level of plasma Hx at rest and after standard exercise may be a useful tool for monitoring the adaptation of energetic processes in different training phases and support the overload/overtraining diagnosis.